Pengembangan Media Pembelajaran Berbasis Video Interaktif pada Materi Sistem Komputer - Emi, Emi; Nurcahyo, Ratih Widya; Septi, Yuri; Fatmawati, Erni (Journal of Multidiscipline and Collaboration Research, 2024)
This study aims to determine how the development of interactive video-based learning media on computer system material in class VII SMPN 1 Mempawah Hulu, assess the feasibility of interactive video-based learning media, and determine student responses to the use of interactive video-based learning media on computer system material. The research method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model for the media feasibility development stage, namely; 2 lecturer media expert validators, and 2 teacher material expert validators. and the test subjects, namely; 30 students of class VII SMP Negeri 1 Mempawah Hulu.  Data collection tools used in this study are; 1) Interview; 2) Questionnaire. Data analysis techniques used: Namely descriptive qualitative and quantitative. The results of the study based on the assessment of media experts obtained a score of 96% media feasibility level and 94% material experts with an average feasibility presentation of 84% which is in the "Very Feasible" category. And for student responses with an average feasibility percentage of 92% which is in the "Strongly Agree" category.